Viscoelastic Methods of Blood Clotting Assessment – A Multidisciplinary Review - Benes, Jan; Zatloukal, Jan; Kletecka, Jakub (Frontiers in Medicine, 2015)
Viscoelastic methods made available the bed-side assessment of blood clotting. Unlike standard laboratory tests, the results are based on the whole blood coagulation, are available in real time and in much faster turnaround time. In combination with our new knowledge about pathophysiology of the trauma induced coagulopathy the goal oriented treatment protocols have been recently proposed for the initial management of bleeding in trauma victims. Besides, the utility of viscoelastic monitoring devices has been proved even outside this setting in cardiosurgical patients or those undergoing liver transplantation. Many other situations were described in literature showing potential use of bed-side analysis of coagulation for the management of bleeding or critically ill patients. In the near future, we may expect further improvement of current bed-side diagnostic tools enabling not only the assessment of secondary hemostasis but also platelet aggregation. More sensitive assays for new anticoagulants are underway. Aim of this review is to offer the reader a multidisciplinary overview on the topic of viscoelastic methods and their potential use in anesthesiology and critical care.